El daimon de la hermenéutica y el reencantamiento del mundo. / The Daimon of Hermeneutics and the Re-Enchantment of the World. - BERIAIN, Josetxo; GARAGALZA, Luis (Utopía y Praxis Latinoamericana, 1970)
RESUMEN La interpretación como modo de ser del ser humano se ocupa en la siguiente investigación en seguirle los pasos a la figura mítica y simbólica del daimon, desde los inicios de la cultura, el individuo carente de alma propia hasta los inicios de la filosofía griega (Sócrates, el daimon como voz interior que incita al diálogo, El banquete, dialéctica entre la razón y las ideas y Diotima, Eros como daimon); el cristianismo, en particular la daimonización y desdaimonización de Jesús hasta las sociedades modernas desencantadas del mundo.ABSTRACT The interpretation as a way of being of the human being deals in the following investigation in following the steps to the mythical and symbolic figure of the daimon, from the beginnings of the culture, the individual lacking of his own soul until the beginnings of Greek philosophy (Socrates, the daimon as an inner voice that encourages dialogue, The banquet, dialectic between reason and ideas and Diotima, Eros as daimon); Christianity, in particular the daimonization and de-modernization of Jesus up to the modern disenchanted societies of the world.